FROM SYMBOLIC CONFLICTS TO CULTURAL COLLABORATION: The Role of Local Intelligence in Indonesian Religious Coexistence - Palawa, Alimuddin Hassan; Masbukin, Masbukin; Salayan, Irwandra (Asia-Pacific Journal on Religion and Society, 2025)
Interreligious relations in Indonesia are often framed through narratives of harmony or overt conflict, while the dynamics of symbolic conflict embedded in everyday social life tend to be overlooked. This article aims to analyze how symbolic interreligious conflicts in Indonesia are mediated and transformed through culturally grounded local intelligence and everyday social practices. Employing a qualitative approach based on literature analysis and conceptual reflection on a range of empirical studies on religious conflict and coexistence in Indonesia, this article examines the forms of symbolic conflict that emerge in ritual contestations, struggles over public space, and the negotiation of religious identities, as well as the cultural mechanisms through which communities mitigate these tensions. The findings demonstrate that interreligious conflict in Indonesia is more frequently manifested as symbolic conflict rather than open physical violence, and that local communities do not rely solely on formal regulations or state intervention in managing such tensions. Instead, they activate forms of local intelligence rooted in local wisdom, everyday social relations, and historical experiences of coexistence. These practices reflect an implicit and contextual form of praxis-based dialogue, functioning as mechanisms of conflict transformation that shift symbolic tensions toward cultural collaboration.